Wajah sastera Melayu Singapura selepas perpisahan dengan Malaysia - Mana Sikana, (Universiti Kebangsaan Malaysia, 2009)
1965 marks a prominent historical era in the Singapore Malay literarary scene. This article discusses the changes and developments of Singapore Malay literature during the lull period after Singapore separates from Malaysia, and how it rose once again in a new socio-political-cultural literary context which promotes its own identity. The writer covers all aspects of its growth and developments through various genres such as poetry, short story, novel, drama, essays and criticism. This analysis collaborate the application of literary theories and approaches used by the writer to discuss the thoughts and authorship of Singapore Malay literary personalities